Emotional Burden, Quality of Life, and Coping Styles in Care Givers of Patients with Disorders of Consciousness Living in Italy: Preliminary Data. Issue 3 (6th December 2016) - Romaniello, Caterina; Simoni, Chiara; Farinelli, Marina; Bertoletti, Erik; Pedone, Vincenzo; Northoff, Georg
Abstract : The literature about the care givers of patients with Disorders of Consciousness (DOCs) has highlighted the impact on both mental and physical dimensions of quality of life. This study aimed to: (1) describe emotional burden, quality of life, and coping styles in care givers of hospitalized patients with DOCs, compared to Italian normative data; (2) explore the relationships between these variables and their associations with socio-demographic features; and (3) describe their changes over time. Fifteen care givers of patients with DOCs, mostly middle-aged women, were assessed using the Family Strain Questionnaire, the SF-36 Health Survey, and the Coping Orientation to Problems Experienced – Nuova Versione Italiana. Eleven subjects were also assessed after 6 and 12 months. Data were analysed through descriptive statistics, correlations, and nonparametric tests of group differences. Compared to the Italian normative data, our sample showed a worse outcome in mental health, social functioning, global mental component, and emotional role functioning. Furthermore, subjects with high emotional burden had more thoughts of death compared to subjects with low emotional burden. Follow-up analyses revealed no variables changed over time. These results highlight the need for psychological interventions and support, since care givers represent an important part of an all-embracing support and care network for patients with DOCs.